River hydrology and recent suspended sediment flux in the Red River: implication for assessing soil erosion and sediment transport/deposition processes - Thi Ha, Dang; Coynel, Alexandra (Vietnam Journal of Science and Technology, 2016)
Based on a database of daily water discharge and daily suspended particulate matter concentrations along the Red River and at the outlet of the main tributaries (Da and Lo) during the 2005-2010 period, covering contrasting hydrological conditions, the water and sediment fluxes transported by the Red River system were determined. The results showed that only 21% of the discharge is derived from the upper Red River, 54% and 25% being derived from the Da and the Lo Rivers, respectively. In contrast, the distribution of suspended particulate matter (SPM) load is very different of that observed for water discharge: most SPM were eroded from the upstream catchment located in China (78%). Moreover, annual SPM fluxes (FSPM) showed a strong spatial variability between upstream watershed and the outlet of the river. The mean inter-annual FSPM was 30 Mt/yr (i.e. specific flux of 741 t/km²/yr) at the LaoCai site, 38 Mt/yr (i.e. 792 t/km²/yr) at the PhuTho gauging site, 29 Mt/yr (i.e. 193 t/km²/yr) at the SonTay gaugng station. Its values were 4.1 Mt/yr (i.e. 80 t/km²/yr) and 6.6 Mt/yr (i.e. 191 t/km²/yr) for the Da and Lo rivers, respectively. Between the LaoCai and PhuTho sites, both erosion and sedimentation processes occurred together, but strongly depended on the hydrological conditions. Between the PhuTho and SonTay sites, the important loss of SPM flux suggested a dominant deposition process in the floodplain during high water before the delta. These results proved the complex processes of erosion/sedimentation occurring on the Red River watershed.